1997
DOI: 10.1093/jac/40.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin resistance in Campylobacter jejuni and Campylobacter coli isolates from Swedish patients

Abstract: This study focused on the frequency of Campylobacter jejuni and Campylobacter coli strains resistant to norfloxacin. Included were 1659 consecutive stool specimens isolated between 1992 and 1995, from as many Swedish patients with diarrhoea. The patients were divided with regard to place of infection and age. All strains were tested for susceptibility to norfloxacin by means of disc diffusion test on blood-agar plates. Norfloxacin-resistant strains (n = 310) were furthermore tested for resistance to doxycyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
0
25
2
1
Order By: Relevance
“…Compared to several other studies (16,18,19), our study showed a tetracycline agent to have a high activity against Campylobacter isolates of domestic origin. However, of the isolates with reduced susceptibility to ciprofloxacin, 54% were inhibited only by high concentrations of doxycycline.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Compared to several other studies (16,18,19), our study showed a tetracycline agent to have a high activity against Campylobacter isolates of domestic origin. However, of the isolates with reduced susceptibility to ciprofloxacin, 54% were inhibited only by high concentrations of doxycycline.…”
contrasting
confidence: 58%
“…In Finland, susceptibility to fluoroquinolones among domestic Campylobacter isolates has remained consistently good (13), as confirmed in the present study. Similarly, in some other countries (Australia and Sweden), fluoroquinolone resistance among domestically acquired campylobacter infections is rare (18,20). This may be explained in some cases by the lack of fluoroquinolone use in food production animals (2,11,20).…”
mentioning
confidence: 99%
“…Intravenous aminoglycosides is the treatment of choice for serious Campylobacter bacteraemia and other systemic infections. However, increases in the occurrence of Campylobacter, causing infections in man, that are resistant to macrolides and fluoroquinolones, have been reported in several countries [13,16,24,45,46,52,55,57]. In these cases other antimicrobial agents may be used for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracycline, doxycycline, and chloramphenicol are sometimes listed as alternative drugs for treatment. However, an increasing number of Campylobacter species that exhibit decreased susceptibility to several of these drugs have been isolated from food and water sources as well as from clinical samples in Europe (9,14,15,18), Canada (5), and the United States (2,17).…”
mentioning
confidence: 99%